Development of a gaseous recoil-proton detector for neutron flux measurements between 0.2 and 2 MeV neutron energy - Marini P.; Mathieu L.; Aiche M.; Cheron T.; Hellmuth P.; Pedroza J.L.; Czajkowski S.; Jurado B.; Tsekhanovich I. (EPJ Web of Conferences, 2017)
Absolute measurements of neutron fluence are an essential prerequisite of neutron-induced cross section measurements, neutron beam lines characterisation and dosimetric investigations. Precise neutron flux measurements can be performed with respect to the H(n,p) elastic cross section. The use of this technique, with silicon proton recoil detectors, is not straightforward below incident neutron energy of 1 MeV, due to a high background in the detected proton spectrum. Experiments carried out at the AIFIRA facility identified its origin. Based on these investigations, a gaseous recoil-proton detector has been designed, with a reduced low energy background. Preliminary results of the first tests of the developed detector are discussed here.